(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article broadly covers the content and pedagogical features of preparing future music teachers for spiritual and educational activities. The problem of forming their knowledge, skills and qualifications in accordance with modern requirements in preparing future music teachers for spiritual and educational activities is discussed.